Wegetatywne bufory środowiskowe w strategii redukcji uciążliwości zapachowej instalacji ippc, na przykładzie projektu pasa zieleni dla składowiska ZUO w Ścinawce Dolnej = Vegetative environmental buffers in mitigation strategy of odour nuisance from ipcc installations, on the example of a shelterbelt project for landfill in Scinawka Dolna, Poland - Kwiecińska, Kornelia; Szałata, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Polish Environmental Law impose a number of specific requirements to landfill administrators, concerning all measures aimed to prevent the landfill from posing a threat to the environment. Vegetative environmental buffers located around odour emitting objects act as biogeochemical barriers for these objects and effectively reduce propagation of malodorous gases to adjacent areas.
Keywords: odory; wegetatywne bufory środowiskowe; pasy zieleni; składowisko odpadów; odour; vegetative environmental buffer; shelterbelt; landfill